Impact of changes in regulatory framework on approval of medicines for rare diseases and applicability to market access policies - Brown, Fran; Vargas, Maximilian; Stanisic, Sanja; Fatzinger, Geoff; Iliach, Oxana (Frontiers in Medicine, 2025)
The introduction of the Orphan Drug Act in the USA in 1983, followed by adoption of the Orphan Drug Regulation No 141/2000 in the EU in 2000, led to a change in landscape of drug development for rare diseases. The introduction of regulations, guidance documents and incentives aimed at increasing the availability of new medicines for rare diseases resulted in an increase in approvals of 3 and 11-fold for branded products and generic medicines, respectively, in the decade 2013–2023 compared to 1990–2000. This effort was successful due to the collaboration of Regulatory Authorities, industry, patient groups and other stakeholders keen to leverage an integrated evidence approach using non-traditional approaches. While the regulatory approval landscape moved toward integration, the effective access to those medicines over the same period was globally fragmented with pricing and access determined at a local level. There is growing recognition of the importance of addressing the needs of rare disease patients and a concerted effort to balance innovation with affordability and access.